DIVERSIFIKASI PEKERJAAN SEBAGAI STRATEGI BERTAHAN HIDUP RUMAH TANGGA NELAYAN DI GALESONG UTARA - Hasriyanti Hasriyanti; Hendra Hendra (Universitas Negeri Gorontalo, 2021)
This study aims to: 1) find out the opportunities for Bontolebang fishermen's households to survive, 2) find out the strategies of fishermen households to survive through job diversification. This type of research is ethnographic qualitative. Data was collected by observation, interviews, and documentation. The data analysis used is qualitative data analysis through the reduction stage, data presentation and conclusion drawing. The results showed that the strategy adopted was an adaptation strategy, and a job diversification strategy by empowering fisherwomen and women-headed households (WKRT) of fishermen, both related to fishing and outside activities. Job diversification opportunities have a dependence on nature that provides resources, so that resource potential is optimized in job diversification alternatives. The diversity of characteristics of the natural environment that each fisherman has. Fishing for fishermen's households is a speculative activity, therefore, fishermen always have an uncertain income. Women become an important part in fulfilling the needs of household life because of the system based on the division of labor. The research implication is that the government, stakeholders and other communities can work together with each other to build policies, or go directly to build fishing villages that are low-income